Determinants of Zakat Compliance among Business Owners in Indonesia - Dahlia Bonang; Muhammad Baihaqi; Martini Dwi Pusparini (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
This study aims to identify the factors that affect the compliance of Indonesian business owners with zakat payments. Data were collected from 205 individuals using a purposive sampling technique through an online survey. The results of the data analysis, conducted using Structural Equation Modeling (SEM), indicate that social piety, zakat literacy, Islamic egalitarianism, and moral norms significantly influence the intentions and compliance of business owners regarding zakat payments. These factors play a crucial role in shaping the intentions and behaviors of business owners concerning their zakat obligations. The findings offer valuable insights for both business owners and policymakers in efforts to improve compliance with zakat payments, which ultimately contributes to economic sustainability and social justice. Business owners can utilize these results to enhance their understanding of zakat obligations, thereby increasing their compliance. For policymakers, the results can serve as a foundation for designing more effective strategies to encourage compliance among business owners, such as implementing zakat literacy programs, socialization activities, and approaches that reinforce the values of egalitarianism and moral norms within the context of zakat.============================================================================================================ABSTRAK – Determinan Kepatuhan Zakat Para Pemilik Bisnis di Indonesia. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi kepatuhan pemilik bisnis Indonesia dalam membayar zakat. Data dikumpulkan dari 205 individu menggunakan teknik sampling purposif melalui survey online. Hasil analisis data dengan Structural Equation Modeling (SEM) menunjukkan bahwa kesalehan sosial, literasi zakat, egalitarianisme Islam, dan norma moral memiliki pengaruh signifikan terhadap intensi dan kepatuhan pemilik bisnis dalam membayar zakat. Faktor-faktor ini memainkan peran penting dalam membentuk niat dan perilaku pemilik bisnis terkait dengan kewajiban zakat. Temuan ini memberikan wawasan yang berharga bagi pemilik bisnis dan pembuat kebijakan dalam upaya meningkatkan kepatuhan pembayaran zakat, yang pada akhirnya berkontribusi pada keberlanjutan ekonomi dan keadilan sosial. Pemilik bisnis di Indonesia dapat menggunakan hasil kajian ini untuk meningkatkan pemahaman mereka tentang kewajiban zakat, sehingga meningkatkan kepatuhan mereka dalam membayar zakat. Bagi pembuat kebijakan, temuan ini dapat dijadikan sebagai dasar untuk merancang strategi yang lebih efektif yang dapat mendorong kepatuhan pemilik bisnis dalam membayar zakat, seperti program literasi zakat, aktivitas sosialisasi, dan pendekatan yang memperkuat nilai-nilai egalitarianisme dan norma moral dalam konteks zakat.